A study of socio economic status and psychological factors potentiates the playing ability among low and high performers of state level football players - SuthakarKrishnaswamy1, AnnidaBalakrishnan2, S.Chandrasekaran1*, A.Anbanandan1, (Journal of Experimental Sciences, 2011)
The purpose of the study was conducted to analyze the playing ability among low and high performers of state level football players by influencing the socio economic status and psychological factors. One hundred and fifty men football players in the age of 20 to 25 years were selected from Tamilnadu state level men football tournament held at Chennai in 2008-09. All the subjects were oriented the purpose of the test and procedure of conducting this test. The selected subjects were randomly divided into three equal groups of each fifty members. Group 1 -Chennai Team, Group-II Salem and Coimbatore Team and Group III Trichy and Madurai Team. Questionnaire preparation was done by our Research Scholar with the reference to the review of the literature. The investigator has focused onto the following variables; socio-economic status, anxiety, and aggression. The data was collected with the help of five PhD Scholars of Department of Physical Education who were well versed with the conduct of test (questionnaire), and collections under the direct supervision of our Research Scholar. Data will be collected before and after the competition through (Questionnaire). After completed the tournament collected the data for post test. During the competition period to assess the three trained express for football players total playing ability to be measured and statistically analyzed using ANOVA and DMRT. The study reveals the effect of socioeconomic and psychological factors in player’s ability in performing the game at low and high level football players. Keywords: Football; Socio-economic status; Anxiety; Aggression